An experimental investigation of the effects of upstream probe disturbance on compressor cascade performance. (June 2017) - Xiang, Honghui; Ge, Ning; Hou, Minjie; Gao, Jie; Yang, Rongfei
An experimental study was conducted in the present study to investigate the effects of upstream probe disturbance on the compressor cascade performance. The experiments were carried out using a plane cascade test facility where the aerodynamic coupling mechanisms between the inner probe and compressor were particularly evaluated in terms of the complex reversed pressure gradient. Moreover, the influence of probe install position near the cascade leading edge on the downstream flow characteristic was evaluated in detail. Results show that the presence of probe at cascade leading edge can reduce the total pressure recovery coefficient, raise the wake loss at cascade outlet and deteriorate the periodicity of conventional cascade flow field distribution. An optimum circumferential installing position at the upstream of the cascade is found with a minimum disturbance, which is not affected by the varying Mach numbers significantly. The probe installed at the intermediate of flow passage has a smaller disturbance on the downstream cascade performance than that installed in front of cascade leading edge.